Pengaruh Substitusi Terigu Dan Tepung Daun Kelor Terhadap Mutu Organoleptik, Kadar Fe, Serat dan Kapasitas Antioksidan Kue Sus - Utami, Komang Dinda Adelya; Puryana, I Gusti Putu Sudita; Tamam, Badrut (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2024)
Choux Pastry is type of pastry that has a soft texture, also can be filled with some filling inside. The aim of the study was to determine the effect of the composition of wheat flour and moringa leaf flour on the organoleptic quality, iron, fiber and antioxidant capacity of choux pastry. The type of research is Randomized Block Design (RBD) with 5 types of treatment, there are P1 (3% moringa leaf flour: 97% wheat flour), P2 (5% moringa leaf powder: 95% wheat flour), P3 (7% moringa leaf flour % : 93% wheat flour), P4 (9% moringa leaf flour : 91% wheat flour), P5 (11% moringa leaf flour : 89% wheat flour) with 3 repetitions. Choux Pastry with different wheat flour and moringa leaf flour substitutions had a significant effect on organoleptic tests and chemical quality including color, scent, texture, taste, overall acceptability, color quality, taste quality, Fe, and antioxidant, but has no significant effect on fiber. The best treatment of Choux Pastry is with 3% moringa leaf flour substitution treatment : 97% wheat flour (P1) was most preferred in terms of taste, texture, scent, color, overall acceptability, taste quality, color quality, Fe of 0,82mg/100g, antioxidant of 0.010%, and fiber of 3.487%.